Pengaruh Fraksi Volume Terhadap Kekuatan Tarik dan Lentur Komposit Resin Berpenguat Serbuk Kayu - Gapsari, Femiana; Setyarini, Putu Hadi (Jurnal Rekayasa Mesin, 2010)
On the research, composite was made from polyester with volume of filler fraction variable of 15%, 30%, 45% and the type of filler was Mahogany (Swietania mahogani). The filler measurement used was 50 mesh. Polymer matrix used was BQTN 157 unsaturated resin polyester. The tensile test of experiment specimen was based on ASTM D638 M-93. and the bending specimen was based on D790-92 Standard. The higest of tensile strength on the volume fraction of 30% that is of 2.081916 kg/mm2 . For the composite material with particle of composite material mahogany with filler volume fraction of 15% had the average flexural strength of 34.98 N/mmÂ². On the particle with volume fraction of 30% had the highest average flexural strength of 45.6780 N/mmÂ². The higest Modulus of Elasticity(E) and Shear Modulus (G) was owned by the composite with filler volume of 635.464 kg/mm2 dan 958.85 MPa Keywords : Composite, volume fraction, tensile strength, flexural strength